Selective isolation of cultivable actinomycetes from thai coastal marine sediment - Ruttanasutja,P. (Chiang Mai University, 2015)
© 2015 Chiang Mai University. All rights reserved. ABSTRACT This study was designed to improve isolation method for actinomycetes from coastal marine sediments. Five pretreatments, three enrichment media, and fifteen selective media were tested for isolation of actinomycetes from a coastal marine sediment sample from Thailand. The pretreatment methods were (1) Tenfold serial dilution, (2) Tenfold serial dilution with 10 minutes shaking at 125 rpm, (3) 1.5% phenol treatment, (4) Shaking sediment suspension for 10 minutes at 125 rpm, and (5) Shaking sediment suspension for 60 minutes at 125 rpm. Three enrichment media were used: (1) Marine Broth (MB), (2) Soil Extract Solution (SES), and (3) Marine Soil Extract Broth (MSB). All culture plates were incubated at 25°C for up to 30 days on 15 selective isolation media. Actinomycetes were isolated only by shaking sediment suspension for 60 minutes at 125 rpm (pretreatment 5). Marine broth was found to promote the isolation of actinomycetes with the highest ratio of total bacteria:actinomycetes (2:1). A total of 209 actinomycetes were isolated. In general, diluted media or low nutrient media were more effective for the isolation of actinomycetes. Molecular identification based on 16S rRNA gene sequences revealed that these isolates belonged to eight known actinomycete genera: Curtobacterium, Dermacoccus, Micromonospora, Microbispora, Pseudonocardia, Rhodococcus, Streptomyces and Tsukamurella.